DOKUMENTASI SISTEM MANAJEMEN MUTU PADA USAHA MIKRO MANTEP KITCHEN JAYA PRODUCTION - Dyah Puspitasari Sunaryo Putri; Ihsan Supono; Prayoga Bakti (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2021)
Coaching the micro-enterprises is one of the Community Service (PKM) activities at Pamulang University. This current activity is the second phase of PKM activity at Mantep Kitchen Jaya Production. The first stage is to provide guidance on awareness of quality management, which introduces and conducts gap analysis on Mantep Kitchen Jaya Production's micro-enterprises in terms of to what extent this micro-business aware of quality management. The result of the analysis is that recommendations are given to improve quality management. One of the recommendations given is that the Mantep Kitchen Jaya Production micro business needs to start implementing a documentation system in accordance with the rules of ISO 9001:2015. Therefore, the second PKM activity is to build awareness of the quality management system documentation. This second phase of activity, which was carried out for 2.5 months, implemented 3 steps: (1) Coordination and Planning, (2) Documentation Adjustment, and (3) ISO 9001 Documentation in the form of forms tailored to the needs of the business partners. With the form that is part of the documentation, the micro business owner of Mantep Kitchen Jaya Production can find out how to apply documentation to the quality management system.Keywords:  Awareness, Quality Management, Documentation